The solution to improve information security for IoT networks by combining lightweight encryption protocols - Nguyen Van Tanh; Ngo Quang Tri; Mai Manh Trung (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
With the strong development of Internet platforms today, many new technologies are applied in most areas of human social life. The development of the internet of things (IoT) has brought to the networking world many innovations with new protocols. Along with that is the complexity of security issues that greatly affect personal data, and limited resources in information technology development and applications. Many security solutions have been researched but none of them is completely effective for the IoT network because of the characteristics of energy, limited resources, processing capacity as well as operating costs. Therefore, we propose an effective solution for comprehensive protection of IoT systems against attacks to network security with improved security protocols. By combining security solutions on the layers of the IoT and code improvement, algorithmic enhancement positively contributes to this important task. In the article, we propose to improve and combine the DTLS Protocol and the overhearing mechanism and then have some experiments to prove the effectiveness, feasibility, economical and appropriate on popular IoT network models.